The effects of two different doses of intravenous dexamethasone on blood glucose concentration intra-operatively and on postoperative pain and emesis in patients undergoing surgery under spinal anesthesia: A double-blind randomized clinical study - Titler, Sanjiv; Gupta, Suman; Ankita Gupta,; Goyal, Shikha; Dilip Kothari, (Asian Journal of Medical Sciences, 2023)
Background: Spinal anesthetic techniques are relatively safe and associated with quick and uneventful recovery, but post-operative pain and postoperative nausea and vomiting (PONV) are major concerns after the effect weans off. Steroids by virtue of their anti-inflammatory effect are expected to reduce pain as well as PONV. Aims and Objectives: The study was conducted to evaluate the efficacy of two different doses of intravenous dexamethasone on blood glucose concentration intra-operatively and on post-operative analgesia and emesis for different surgeries under spinal anesthesia. Materials and Methods: This double-blind randomized clinical study was performed on 120 patients aged 20–60 year posted for surgery under spinal anesthesia who were randomly allocated into three groups to receive either normal saline (Group A: 40 pts), intravenous 4 mg dexamethasone (Group B: 40 pts), or iv 8 mg dexamethasone (Group C: 40 pts) immediately after spinal anesthesia. Hemodynamic parameters, respiratory rate, intraoperative blood glucose concentration., severity of post-operative pain, and incidence of PONV was compared among the groups. Results: Patients in Group C had significantly less severe post-operative pain and incidence of PONV (P<0.05). Furthermore, less post-operative rescue analgesia was required in Group C (P<0.05). There was a highly significant rise in intraoperative blood glucose level in Group C as compared to other groups, but it was well below the recommended guidelines (<180 mg/dL). Conclusion: Our study concluded that i.v. dexamethasone 8 mg was more effective, although it caused raised blood glucose concentration intraoperatively, but it also provided prolonged post-operative analgesia, increased time of first rescue analgesic, less incident of post-operative nausea and vomiting, and better patient satisfaction.